"Reasonable" Force at the U.S.-Mexico Border. (20th July 2021) - Vega, Irene I
Abstract: While social scientists have studied the relationship between police culture and use of force for decades, federal immigration agents have been left out of these analyses. Addressing this gap is urgent given patterns of excessive force at the militarized U.S.-Mexico border. Drawing on bureaucratic documents and interviews with active Border Patrol agents, this article examines the culture of force within this organization. I show that the Border Patrol produces a sense of exceptional threat and power among agents through 1) narratives that construct the border as a uniquely dangerous work environment, and 2) lessons that encourage an overly-individualistic view of reasonableness, the constitutional standard that governs police force in the United States. Together, these organizational messages foster in agents a disproportionate sense of threat coupled with an awareness of the low probability of legal sanction for force violations. This paradoxical combination of vulnerability and power undergirds agents' conceptions of their force authority.